Future scenarios of palliative care in health system of Iran: a multi-method study - Barasteh, Salman; Parandeh, Akram; Rassouli, Maryam; Zaboli, Rohallah; Vahedian Azimi, Amir; Khaghanizadeh, Morteza (Frontiers in Public Health, 2024)
Paying attention to palliative care has accelerated in Iran in the last ten years. Considering the trend of aging, increasing burden of chronic diseases and increasing health costs, planning and development of palliative care is necessary in the future. This study was conducted with the aim of explaining the alternative scenarios of palliative care in the health system of Iran until the horizon of 2030.This study was a multi-method scenario planning with a qualitative using multiple methods design, which was conducted in 3 phases in 2018-2020. In the first phase, a list of driving forces was extracted using qualitative interviews and literature review. In the second phase, all factors identified in the previous phase were examined in terms of degree of uncertainty and cross-impact analysis, and two key uncertainties were extracted. In the third phase, based on two key uncertainties, four future scenarios of palliative care were formulated, validated and scenario strategies were presented.